Our Australian girl - Hamer, Michelle (Puffin, 2014)
It's 1930 . . . and Daisy has finally had news that her dad is alive! He's gravely injured somewhere in the bush, and though she doesn't know quite where, Daisy is determined to find him. With help from old friends, she sets off on her way. But life on the road is hard, and before long, disaster strikes . . . Will Daisy reach Dad before it's too late? Follow Daisy on her adventure in the final of four exciting books about a hopeful girl in troubled times